Pemanfaatan Barang Bekas untuk Membuat Media Pembelajaran dalam Mewujudkan Sekolah yang Asri - Sri Yanti; Nita Priyanti; Chandra Apriyansyah (EduInovasi: Journal of Basic Educational Studies, 2025)
The purpose of this study was to analyze the utilization of used goods and analyze the obstacles and efforts to overcome them at the Imam Asy-Syafi'i Islamic Kindergarten, Setu, Bekasi. The research method used a qualitative approach with a case study method. Data collection techniques used interview instruments, observation, and documentation. Data analysis techniques through the stages of data collection, data reduction, data presentation, verification and confirmation of conclusions. Data examination and validity used triangulation methods. The results of the study showed that a) the utilization of used goods in the form of plastic bottles and bottle caps was used as a learning medium to create a beautiful school garden at the Imam Asy-Syafi'i Islamic Kindergarten, Setu, Bekasi. Used plastic bottles and bottle caps are child-friendly items, easy to do and safe for children; b) The steps for utilizing used goods to create learning media and a beautiful school begin with preparing a learning media design that refers to the curriculum or teaching materials and meets the requirements, then making a learning plan; c) obstacles in the utilization of goods are the lack of availability of used goods that can be used to make learning media and the lack of experts to organize a fairly large school garden to become a child-friendly and beautiful garden; d) efforts made to overcome obstacles in the utilization of used goods in TK Islam Imam Asy-Syafi'i Setu, namely the cooperation of the school with parents of students and the surrounding community to collect used goods, create learning media, and organize a beautiful school garden. Keywords: utilization of used goods, learning media, early childhood education, school garden ABSTRAK Tujuan penelitian ini untuk menganalisis pemanfaatan barang bekas dan menganalisis hambatan serta upaya mengatasinya di TK Islam Imam Asy-Syafi'i, Setu, Bekasi. Metode penelitian menggunakan pendekatan kualitatif dengan metode studi kasus. Teknik pengumpulan data menggunakan instrument wawancara, observasi, dan dokumentasi. Teknik analisis data melalui tahapan pengumpulan data, reduksi data, penyajian data, verifikasi dan penegasan kesimpulan. Pemeriksaan dan keabsahan data menggunakan triangulasi metode. Hasil penelitian menunjukkan bahwa a)pemanfaatan barang bekas berupa botol dan tutup botol pastik digunakan sebagai media pembelajaran untuk menciptakan taman sekolah yang asri di TK Islam Imam Asy-Syafi'i, Setu, Bekasi. Botol dan tutup botol plastik bekas merupakan barang yang ramah anak, mudah dilakukan dan aman bagi anak; b)Langkah-langkah pemanfaatan barang bekas untuk membuat media pembelajaran dan sekolah yang asri diawali dengan penyiapan desain media pembelajaran yang merujuk pada kurikulum atau bahan ajar dan memenuhi persyaratan, kemudian membuat rencana pembelajaran; c) hambatan dalam pemanfaatan barang adalah kurangnya tersedianya barang bekas yang dapat digunakan untuk membuat media pembelajaran dan kurangnya tenaga ahli untuk menata taman sekolah yang cukup luas agar menjadi taman yang ramah anak dan asri; d) upaya yang dilakukan untuk mengatasi hambatan dalam pemanfaatan barang bekas di TK Islam Imam Asy-Syafi'i Setu, yakni adanya kerja sama sekolah dengan orang tua siswa serta masyarakat sekitar untuk mengumpulkan barang bekas, membuat media pembelajaran, dan menata taman sekolah yang asri. Kata kunci: pemanfaatan barang bekas, media pembelajaran, pendidikan anak usia dini, taman sekolah